Enriched-GWAS and transcriptome analysis to refine and characterize a major QTL for anaerobic germination tolerance in rice - Tnani, Hedia; Chebotarov, Dmytro; Thapa, Ranjita; Ignacio, John Carlos I.; Israel, Walter K.; Quilloy, Fergie A.; Dixit, Shalabh; Septiningsih, Endang M.; Kretzschmar, Tobias (MDPI, 2021)
Tolerance of anaerobic germination (AG) is a key trait in the development of direct seeded rice. Through rapid and sustained coleoptile elongation, AG tolerance enables robust seedling establishment under flooded conditions. Previous attempts to fine map and characterize AG2 (qAG7.1), a major centromere-spanning AG tolerance QTL, derived from the indica variety Ma-Zhan Red, have failed. Here, a novel approach of “enriched haplotype” genome-wide association study based on the Ma-Zhan Red haplotype in the AG2 region was successfully used to narrow down AG2 from more than 7 Mb to less than 0.7 Mb. The AG2 peak region contained 27 genes, including the Rc gene, responsible for red pericarp development in pigmented rice. Through comparative variant and transcriptome analysis between AG tolerant donors and susceptible accessions several candidate genes potentially controlling AG2 were identified, among them several regulatory genes. Genome-wide comparative transcriptome analysis suggested differential regulation of sugar metabolism, particularly trehalose metabolism, as well as differential regulation of cell wall modification and chloroplast development to be implicated in AG tolerance mechanisms.